1986
DOI: 10.1111/j.1432-1033.1986.tb09419.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a hexaheme cytochrome C552 from Escherichia coli K 12 and its properties as a nitrite reductase

Abstract: Anaerobic cytochrome c 5 5 2 was purified to electrophoretic homogeneity by ion-exchange chromatography and gel filtration from a mutant of Escherichiu coli K 12 that synthesizes an increased amount of this pigment. Several molecular and enzymatic properties of the cytochrome were investigated. Its relative molecular mass was determined to be 69000 by sodium dodecyl sulfate/polyacrylamide gel electrophoresis. It was found to be an acidic protein that existed in the monomeric form in the native state. From its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
77
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 39 publications
6
77
0
Order By: Relevance
“…Subsequently, similar cytochromes were isolated from a variety of anaerobic bacteria and, on the basis of their similar sizes, specific activities, spectra and epr properties were classified as a family of hexahaem nitrite reductases (Liu and Peck, 1981;Blackmore et al, 1986;Kajie and Anraku, 1986;Sadana et al, 1986;Liu et al, 1988;Costa et al, 1990;Schumacher and Kroneck, 1991). This view became untenable when the sequence of the E. coli enzyme became available and revealed the presence of only 10 cysteine residues, eight of which were arranged as conventional CXXCH haem-binding motifs (Darwin et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, similar cytochromes were isolated from a variety of anaerobic bacteria and, on the basis of their similar sizes, specific activities, spectra and epr properties were classified as a family of hexahaem nitrite reductases (Liu and Peck, 1981;Blackmore et al, 1986;Kajie and Anraku, 1986;Sadana et al, 1986;Liu et al, 1988;Costa et al, 1990;Schumacher and Kroneck, 1991). This view became untenable when the sequence of the E. coli enzyme became available and revealed the presence of only 10 cysteine residues, eight of which were arranged as conventional CXXCH haem-binding motifs (Darwin et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to express cytochrome C3 in functional form in Escherichia coli under aerobic or anaerobic growth conditions were unsuccessful because of the inability of E. coli to insert the hemes (19). E. coli does express multiheme c-type cytochromes (e.g., a hexahemoprotein [nitrite reductase] is expressed when nitrate is the terminal oxidant [14]), and its inability to produce holo-cytochrome C3 under these same conditions points to a possible specificity of the heme insertion system. It is therefore appropriate to test more closely related hosts (e.g., D. desulfuricans G200 [8]) for their potential to produce holo-cytochrome C3.…”
mentioning
confidence: 99%
“…The objectives of the characterization of the three cytochromes C3 were (i) to define the properties of the G200 cytochrome C3, which has not been purified before, and (ii) to determine whether the Hildenborough cytochrome C3 produced by the G200 strain (the recombinant protein) was the same as that synthesized by D. vulgaris Hildenborough (the native protein). All three isolated proteins migrated as single polypeptides with apparent molecular weights of 14 kilodaltons during sodium dodecyl sulfate-gel electrophoresis (not shown). Isoelectric focusing using a PHAST GEL apparatus from Pharmacia LKB Biotechnology (11) with Phast Gel IEF 3-9 and a Pharmacia Broad Range pl Calibration Kit, containing proteins with isoelectric points ranging from 3 to 10, indicated a pl of 5.8 for the G200 protein ( Table 2).…”
mentioning
confidence: 99%
“…Nitrite, NO⅐, and hydroxylamine are each reduced stoichiometrically to ammonium such that no intermediates are detectable (15)(16)(17)(18)(19). Because all three substrates form the same product it has been suggested that NO⅐ and hydroxylamine are intermediates during nitrite reduction.…”
Section: No⅐ Hydroxylaminementioning
confidence: 99%
“…Quinol oxidation is catalyzed by NrfD and electrons are transferred, most likely via NrfC and NrfB, to NrfA, a homodimeric, deca-heme-containing cytochrome c nitrite reductase (15). NrfA homologs are present in a wide range of bacteria, and in vitro they have been shown to reduce not only nitrite but also NO⅐ and hydroxylamine to ammonium without releasing detectable intermediates (15)(16)(17)(18)(19). As a consequence, it was proposed that NO⅐ reduction by NrfA, rather than nonspecific reduction by another Nrf component, was responsible for providing E. coli with resistance toward NO⅐ under anaerobic conditions (6).…”
mentioning
confidence: 99%